Barriers and Institutional Dynamics in Public Mental Health Across Income Groups - Xu, Xinran (Simen Owen Academic Proceedings Series, 2025)
Public Mental Health (PMH) has increasingly attracted global attention, yet substantial disparities in its implementation persist between high-income countries (HICs) and low- and middle-income countries (LMICs). As the global burden of mental disorders continues to rise, many countries-particularly LMICs-face challenges including limited institutional capacity, workforce shortages, and fragmented policies. This study examines institutional dynamics, barriers, and engagement practices in PMH across income groups, aiming to identify structural strengths and weaknesses that shape organizational contributions. A cross-sectional survey was conducted with 242 respondents from 52 countries, classified according to World Bank income groups. Participants evaluated key PMH components, opportunities, barriers, engagement frequency, and training quality. Statistical analyses included descriptive comparisons, ANOVA, correlation, and linear regression models stratified by income level. While strategic PMH priorities show broad convergence, significant disparities remain in institutional capacity and implementation readiness. Effective PMH reform must therefore be context-sensitive, emphasizing strengthened knowledge systems and networks in LMICs, alongside continued investment in high-quality training infrastructure in HICs. The advancement of global PMH will depend on scalable strategies that address these structural asymmetries.